Cellulose supported cuprous iodide nanoparticles (Cell-CuI NPs): a new heterogeneous and recyclable catalyst for the one pot synthesis of 1,4-disubstituted-1,2,3-triazoles in water - Chavan, Pramod V.; Pandit, Kapil S.; Desai, Uday V.; Kulkarni, Makarand A.; Wadgaonkar, Prakash P. (RSC Advances, 2014)
Cellulose supported cuprous iodide nanoparticles (Cell-CuI NPs) have been demonstrated for the first time as an efficient heterogeneous catalyst in the click synthesis of 1,4-disubstituted 1,2,3-triazoles by a one-pot three component reaction between aralkyl/alkyl bromides, alkynes and sodium azide in water. The catalyst has been characterized by XRD, HRTEM, SEM, ICP-AES, EDS as well as IR spectroscopy. It was found to be reusable for five consecutive runs without significant loss of activity.

Cobalt ferrite nanoparticles: a magnetically separable and reusable catalyst for Petasis-Borono-Mannich reaction - Kulkarni, Aparna M.; Pandit, Kapil S.; Chavan, Pramod V.; Desai, Uday V.; Wadgaonkar, Prakash P. (RSC Advances, 2015)
Magnetically separable cobalt ferrite nanoparticles (CoFe2O4, NPS) have been demonstrated for the first time as an efficient catalyst in Petasis-Borono-Mannich (PBM) reaction between salicylaldehydes, sec. amines and aryl boronic acids to furnish alkylaminophenols in high yields. Relatively shorter reaction times, easy purification of the products and reusability of the catalyst for five consecutive runs without appreciable loss in it's activity are the noteworthy features of the developed protocol.

Click-chemistry-based multicomponent condensation approach for design and synthesis of spirochromene-tethered 1,2,3-triazoles as potential antitubercular agents - Chavan, Pramod V.; Pandit, Kapil S.; Desai, Uday V.; Wadgaonkar, Prakash P.; Nawale, Laxman; Bhansali, Sujit; Sarkar, Dhiman (Research on Chemical Intermediates, 2017)